Development and dependency in the periphery: From bananas to tourism in Bocas del Toro, Panama. (December 2021) - Pleasant, Traben; Spalding, Ana
Highlights: Like US-Panama dealings, the UFC exploited Black and Indigenous laborers' dependency. UFC-Bocas was centralized. Now, decentralized insecure tourism drives Bocas' economy. From UFC bananas to tourism, local dependence on US/EU enterprise in Bocas continues. Abstract: Many development outcomes in Latin America and the Caribbean are linked to geopolitical economic systems, available technologies, and legacies of foreign economic dependence. In this article, the core (the U.S.), the periphery (Panama), and Panama's own internal periphery (the District of Bocas del Toro), represent an interrelated global capitalist system that inherently maintains periphery marginality through exploitation and dependency over time. We illustrate this core-to-periphery phenomenon through two inextricably linked examples. Example one is the United Fruit Company's (UFC) twentieth century era of economic dominance in the Central American banana industry, its operations, and historical impacts on Bocas del Toro, Panama (also called Bocas). Example two is the tourism industry in Bocas, particularly the late 1990s tourism boom that continues to dominate its economy today. Each example—the banana industry then and the tourism industry now—involve eras of dependence on U.S./European dominated industries. Using primary and archival data, we analyze and contrast the two distinct periods, the wellbeing of Black and Indigenous people, and contemporary development trends in Bocas (e.g., lifestyle migration/expats, residential tourism and technology). We also use labor and employment (or a lack thereof) as important indicators of local wellbeing. We show that the past record of economic dependence on the UFC in Bocas is linked to its current record of economic dependence on tourism. We suggest that tourism, as a modern neoliberal endeavor in Latin America and the Caribbean, can be deeply rooted in a history of dependency on U.S./European dominated industries and development practices.